Hepatitis E: An update on One Health and clinical medicine. (19th May 2021) - Velavan, Thirumalaisamy P.; Pallerla, Srinivas R.; Johne, Reimar; Todt, Daniel; Steinmann, Eike; Schemmerer, Mathias; Wenzel, Jürgen J.; Hofmann, Jörg; Shih, James Wai Kuo; Wedemeyer, Heiner; Bock, Claus‐Thomas
Abstract: The hepatitis E virus (HEV) is one of the main causes of acute hepatitis and the de facto global burden is underestimated. HEV‐related clinical complications are often undetected and are not considered in the differential diagnosis. Convincing findings from studies suggest that HEV is clinically relevant not only in developing countries but also in industrialized countries. Eight HEV genotypes (HEV‐1 to HEV‐8) with different human and animal hosts and other HEV‐related viruses are in circulation. Transmission routes vary by genotype and location, with large waterborne outbreaks in developing countries and zoonotic food‐borne infections in developed countries. An acute infection can be aggravated in pregnant women, organ transplant recipients, patients with pre‐existing liver disease and immunosuppressed patients. HEV during pregnancy affects the fetus and newborn with an increased risk of vertical transmission, preterm and stillbirth, neonatal jaundice and miscarriage. Hepatitis E is associated with extrahepatic manifestations that include neurological disorders such as neuralgic amyotrophy, Guillain‐Barré syndrome and encephalitis, renal injury and haematological disorders. The risk of transfusion‐transmitted HEV is increasingly recognized in Western countries where the risk may be because of a zoonosis. RNA testing of blood components is essential to determine the risk of transfusion‐transmitted HEV. There are currently no approved drugs or vaccines for HEV infections. This review focuses on updating the latest developments in zoonoses, screening and diagnostics, drugs in use and under development, and vaccines.